(untitled) (Perner’s Contacts, 2021)
There is currently available no public logistics center in the Czech Republic. The roads infrastructure in the Czech Republic are overloaded by freight transportation and at the same time railways are underused for freight transportation, water flows for freight transport are used negligible due to still delayed realization of yearround navigability the Elbe River. It is necessary to analyze the possibility of realization and to find the optimal variant. Future end port on the Elbe River in the city of Pardubice (Czech Republic) is a long-term prepared project. It is closely related to the project of ensuring year-round navigability of the Elbe River and of ensuring waterways to the seaport of Hamburg and other northern seaports. The European Commission introduced on October 19, 2011 a plan to improve Europe’s transport, energy and digital networks (new Trans-European Transport Network (TEN-T). This plan included Elbe waterway with the end port in Pardubice between projects of the main network.